2021
DOI: 10.1002/1873-3468.14251
|View full text |Cite
|
Sign up to set email alerts
|

Roles of peripheral clocks: lessons from the fly

Abstract: To adapt to and anticipate rhythmic changes in the environment such as daily light-dark and temperature cycles, internal timekeeping mechanisms called biological clocks evolved in a diverse set of organisms, from unicellular bacteria to humans. These biological clocks play critical roles in organisms' fitness and survival by temporally aligning physiological and behavioral processes to the external cues. The central clock is located in a small subset of neurons in the brain and drives daily activity rhythms, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 316 publications
(428 reference statements)
0
10
0
Order By: Relevance
“…We suspect that HS- Clk jrk , loss of Pdp1ε , and DD likewise have negligible effects on sleep and circadian locomotor activity, consistent with what Inami et al reported for DD. It seems more likely that our effects are mediated by circadian involvement in “other” processes, perhaps ones that recruit “peripheral clocks” (Hardin et al, 2003 ; Ito and Tomioka, 2016 ; Sehgal, 2016 ; Di Cara and King-Jones, 2016 ; Selcho et al, 2017 ; Yildirim et al, 2022 ). Although our results do not clarify all the outstanding issues, they do provide an experimental template going forward to help resolve the current uncertainties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that HS- Clk jrk , loss of Pdp1ε , and DD likewise have negligible effects on sleep and circadian locomotor activity, consistent with what Inami et al reported for DD. It seems more likely that our effects are mediated by circadian involvement in “other” processes, perhaps ones that recruit “peripheral clocks” (Hardin et al, 2003 ; Ito and Tomioka, 2016 ; Sehgal, 2016 ; Di Cara and King-Jones, 2016 ; Selcho et al, 2017 ; Yildirim et al, 2022 ). Although our results do not clarify all the outstanding issues, they do provide an experimental template going forward to help resolve the current uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…The elucidation of the genes, logic, and feedback loops that constitute most eukaryotic molecular clocks has not only extended our knowledge to the mechanistic, molecular level, but reemphasized how pervasive and conserved the functions of the clock are in biology. One outstanding problem in the field is understanding the relationship between the central clock and the different “peripheral clocks” that regulate specific physiological processes (Hardin et al, 2003 ; Ito and Tomioka, 2016 ; Sehgal, 2016 ; Di Cara and King-Jones, 2016 ; Selcho et al, 2017 ; Yildirim et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circadian clocks in land organisms are the only clocks currently understood in molecular mechanistic detail. Whereas animals, plants, and fungi all rely on transcriptional/ translational feedback loops (TTFLs) for their central clock machinery, and phosphorylation/ dephosphorylation cycles play critical roles, the exact molecular factors in these three groups are not homologous or show sequence similarities only to a limited extent (Brenna & Albrecht 2020, Narasimamurthy & Virshup 2021, Saini et al 2019, Yan et al 2021, Yildirim et al 2022. Furthermore, non-TTFL-based ∼24-h oscillatory systems also exist.…”
Section: Cycles Of the Sun And Moon Cause A Multitude Of Biological R...mentioning
confidence: 99%
“…In coordination with processes that are regulated by posttranscriptional mechanisms, clock-regulated rhythmic gene expression programs that are often tissue-and cell-specific produce daily rhythms in clock outputs. The outputs of animal circadian clocks are all-encompassing and include rhythmic processes such as sleep-wake cycles, feeding-fasting cycles, metabolism, hormone production and secretion, immune response, neuronal excitability and even permeability of the blood-brain barrier [3][4][5][6][7][8][9][10]. There is growing evidence that some clock outputs are themselves zeitgebers (i.e.…”
Section: Introductionmentioning
confidence: 99%